Failure analysis of the suspension spring of a light duty truck - Eryürek, I.B.; Ereke, M.; Göksenli, A. (Elsevier BV, 2007)
In this paper the failure of the rear suspension spring is analyzed in detail. The rear axle suspension system of the truck and fractured flat spring is investigated. Fracture surface, mechanical and chemical properties and microstructure of the spring material is analyzed. Forces acting on the spring is determined and strength calculations are carried out. Later, failure behaviour and cause of fracture is revealed after carefully analysis of microstructure and results of calculations. At the end precautions to be taken to prevent a similar failure is recommended.